Introduction of Application of Rubber Tapping Technology and Its Impact on Production of Mekar Tani Groups in Sari Laba Jahe Village, Deli Serdang District - Sumihar Hutapea; Ellen Panggabean; Rizal Azis; Tumpal HS Siregar; Suswati Suswati (Budapest International Research and Critics University, 2020)
The increase of rubber production can be done by introducing tapping technology for rubber farmers, when rubber prices are low. The facts showed that smallholder rubber production is still low, in the range of 600-800 kg of dry rubber / ha / year. Tapping practiced by rubber farmers is generally not based on tapping technology, which is integrated in the aspects of plants, tapping planning and management, the use of stimulants, and a number of other technical aspects. To increase smallholder rubber production, rubber tapping technology was introduced to Mekar Tani Groups in Sari Laba Jahe Village, Sibiru Biru Sub-district, Deli Serdang District (North Sumatra). The results of the introduction in the form of stimulant application showed that a month after applying the stimulant, the increase in production averaged 60.65%. If production without applying the stimulant was 0.18 kg / tree, then after applying the stimulant 0.28 kg / tree was obtain. The results of this study within a month were still continuing to observe other aspects such as the quality of rubber produced due to the application of stimulants, as well as farmers' income.